Understanding Multicellularity: The Functional Organization of the Intercellular Space - Bich, Leonardo; Pradeu, Thomas; Moreau, Jean-François (Frontiers in Physiology, 2019)
The aim of this paper is to provide a theoretical framework to understand how multicellular systems realise functionally integrated physiological entities by organising their intercellular space. From a perspective centred on physiology and integration, biological systems are often characterised as organised in such a way that they realise metabolic self-production and self-maintenance. The existence and activity of their components rely on the network they realise and on the continuous management of the exchange of matter and energy with their environment. One of the virtues of the organismic approach focused on organisation is that it can provide an understanding of how biological systems are functionally integrated into coherent wholes. Organismic frameworks have been primarily developed by focusing on unicellular life. Multicellularity, however, presents additional challenges to our understanding of biological systems, related to how cells are capable to live together in higher-order entities, in such a way that some of their features and behaviours are constrained and controlled by the system they realise. Whereas most accounts of multicellularity focus on cell differentiation and increase in size as the main elements to understand biological systems at this level of organisation, we argue that these factors are insufficient to provide an understanding of how cells are physically and functionally integrated in a coherent system. Our thesis is that one of the fundamental theoretical principles to understand multicellularity, which is missing or underdeveloped in current accounts, is the functional organisation of the intercellular space. In our view, the capability to be organised in space plays a central role in this context, as it enables cell differentiation and increase in size, and even specialised functions such as immunity. We argue that the extracellular matrix plays a crucial active role in this respect, as an evolutionary ancient and specific (non-cellular) control subsystem that contributes to the functional specification of the multicellular space and to modulate cell fate and behaviour. We also analyse how multicellular systems exert control upon internal movement and communication. Finally, we show how the organisation of space is involved in some of the failures of multicellular organisation, such as aging and cancer.